2005
DOI: 10.1200/jco.2005.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Role of the CDKN2A Locus in Patients With Multiple Primary Melanomas

Abstract: MPM patients are good candidates for CDKN2A mutational screening. These patients and some of their siblings should be included in a program of specific follow-up with total body photography and digital dermoscopy, which will result in the early detection of melanoma in this subset of high-risk patients and improve phenotypic characterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
111
3
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 130 publications
(130 citation statements)
references
References 36 publications
14
111
3
2
Order By: Relevance
“…The known SNP, A148T found in three tumors (5%) is reported in 6% of the global and 3% of the European population (http://www.ncbi.nlm.nih.gov/ SNP/snp_ref.cgi?rsZ3731249). It has also been reported as a predisposing alteration in connection to malignant melanoma and breast and lung cancer (Debniak et al 2005, Puig et al 2005. None of the detected sequence alterations occurred in conjunction with malignant disease.…”
Section: Discussionmentioning
confidence: 95%
“…The known SNP, A148T found in three tumors (5%) is reported in 6% of the global and 3% of the European population (http://www.ncbi.nlm.nih.gov/ SNP/snp_ref.cgi?rsZ3731249). It has also been reported as a predisposing alteration in connection to malignant melanoma and breast and lung cancer (Debniak et al 2005, Puig et al 2005. None of the detected sequence alterations occurred in conjunction with malignant disease.…”
Section: Discussionmentioning
confidence: 95%
“…25 The finding that there was no difference in tumor proliferation between the 2 groups measured according to the mitotic rate suggests that melanomas in patients with SPM and MPM may not differ in terms of biologic , both of which function as cell-cycle inhibitors. 34 It has been estimated that germline mutations in CDKN2A occur in 8.3% to 15% of patients with MPM. 10,34,35 In a population-based, case-control study, Berwick et al reported a relative risk of 4.3 for a functionally relevant mutation in CDKN2A in patients with MPM versus patients with SPM.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in diseases such as pancreatic cancer or melanoma, loss of p16 ink4a is a relatively common event. 37 For example, in pancreatic intraepithelial neoplasia (PanIN), a well-defined precursor to invasive pancreatic carcinoma, genetic loss or epigenetic silencing of p16 ink4a follows KRAS mutations and is directly associated with progression to invasive disease. 38 It has been hypothesized that the loss of p16 ink4a is associated with a potent selection to bypass senescence that is ostensibly initiated by the oncogenic insult.…”
Section: Prognostic Features Of P16 Ink4a In Tumorsmentioning
confidence: 99%